Case report: Paracorporeal lung assist device for 215 days as a bridge-to-lung transplantation in a patient with bronchopulmonary dysplasia and severe pulmonary hypertension - Michel, Sebastian G.; Hanuna, Maja; Pattathu, Joseph; Pabst von Ohain, Jelena; Schneider, Christian; Kauke, Theresa; Kneidinger, Nikolaus; Behr, Juergen; Milger, Katrin; Barton, Juergen; Veit, Tobias; Kamla, Christine; et al. (Frontiers in Transplantation, 2023)
Pulmonary hypertension (PH) is a known and life limiting complication of preterm born young adults with bronchopulmonary dysplasia (BPD), ultimately leading to progressive right ventricular (RV) failure. Prognosis remains poor, especially in patients unresponsive to modern vasoactive pharmacotherapy. Therefore, lung transplantation presents the treatment of choice to avert cardiac failure. With limited donor organ availability and long waiting times, the implantation of a paracorporeal lung assist device (PLAD) is a way to bridge the patient as an alternative to veno-arterial ECMO. Herein, we present the case of a prematurely born 23-year-old female, who developed severe PH due to BPD and consequently experienced therapy refractory RV failure. Urgent PLAD implantation was performed and the patient successfully underwent double-lung transplantation after 215 days of PLAD support. No major PLAD-associated complications occurred and full recovery of RV function could be observed after double-lung transplantation.